PENERAPAN LAPORAN REALISASI ANGGARAN BERBASIS KAS MENURUT SAP PP NO. 71 TAHUN 2010 UNTUK MEMENUHI TUJUAN TRANSPARANSI DAN AKUNTABILITAS PENGELOLAAN DANA BOS - Amelia, Ayu Rizky (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2014)
This research was conducted in SDN Candirenggo III Singosari Malang. This study aims to determine the suitability of the budget realization reports BOS funds made by the school with rules on government accounting standards PP No. 71 of 2010, and to know fulfillment the elements of transparency and accountability in accordance with the provisions of the management BOS funds. This research is the explanation and data collection techniques in this study were interviews and surveys. This study analyzed using a disclosure index that measures the disclosure index used to assess compliance with applicable regulations and standards. The result showed, BOS budget realization report SDN Candirenggo III Singosari accordance with the rules of government accounting standards PP No. 71 Year 2010 and SDN Candirenggo III Singosari has met the elements of transparency and accountability. This can be realized thanks to the cooperation of various parties, namely the school, the school committee and parents. For further research is expected to add another criteria to the disclosure of financial statements such as the relevance and reliability of financial statements or researchers can also examine other financial statements, the statements contained in such schools help poor students (BSM Funds).